COMPARISON OF BRITISH AND AMERICAN ENGLISH - Ibayev Anvar Jurabekovich,; Aktamova Dilnoza Bozorboy qizi,; Zokirova Sevinch Quvonchbek qizi,; Beknazarova Dinara Matlubjon qizi,; Boliqulova Muxlisa Nomoz qizi,; Ismatullayeva Bahora G’aybulla qizi, (TADQIQOTLAR, 2026)
Abstract: This study compares British English and American English, two of the most widely used standardized forms of English. Even though they come from the same place in history, hundreds of years of being apart, developing their own cultures, and  setting  their  own  standards  have  caused  big  differences  at  different  levels  of language.  The  study  investigates  variations  in  pronunciation, lexicon,  orthography, syntax, and pragmatic application. Special attention is paid to phonological features like  rhotic  and  non-rhotic  pronunciation,  lexical  differences  between  everyday  and institutional  language,  orthographic  differences  caused  by  historical  changes,  and grammatical differences in how tense is used, how prepositions are used, and how collective nouns are used. The study also looks at the historical reasons why the two varieties diverged, such as the role of language planning and lexicography in the US and the preservation of traditional norms in Britain. Even though there are differences between British and American English, they are still understandable to each other and are used as main models in teaching English around the world. The results show that comparing these two types of language is important for understanding how languages change, improving communication between cultures, and helping people learn foreign languages more effectively.